Presentation of the Postgraduate Course in Music Therapy and the Autism Spectrum: Training and Specialization for Music Therapists in Latin America - Marsimian, Nuria Inés Alicia; Nuzzi, Mariana (Voices: A World Forum for Music Therapy, 2025)
In this article, the directors of the training program and authors of this paper describe the main features of the Postgraduate Course in Music Therapy and Autism Spectrum, a postgraduate academic program designed to train music therapists to provide care to children and adolescents on the autism spectrum. The training has been offered since 2014 at the Italian Hospital University of Buenos Aires (U.H.I.B.A.), with nine nine editionsplanned through 2024. It is based on the conceptualization, systematization, and practical application of different models and approaches, as well as methods and interventions, and takes as its starting point the clinical experience acquired with the population. Significant events related to the beginnings and development of the training program are mentioned, as well as the thematic units of the study program, the teaching-learning methodologies implemented, the assessment of the students, and the construction of evidence in the Latin American region. The main purpose is to sharethe experience gained in its creation and impact on the local and regional community, as well as to report on the challenges encountered. Also,that it can be taken as a reference that inspires and promotes the development of future training programs for music therapists, seeking specialization in the discipline in various areas of application and with different populations. Editorial Comment The issue of academic training represents an enormous challenge for Latin America. Many colleagues who have studied in Europe and the United States return to their countries of origin to practice their profession. Often, those who wish to study music therapy move from small towns to capital cities to pursue higher education and then return to their hometowns. How does this learning experience unfold, between uprooting and returning home?The authors of this paper describe the process of creating a postgraduate course in Argentina, which was facilitated by the hybrid format imposed by the COVID-19 pandemic. It is an example of the virtuous effects of the hyperconnected world in which we live, where disciplinary knowledge spreads very quickly and where we are invited to critically appropriate it, attentive to the uniqueness of the situationsin which we practice our profession.